2016
DOI: 10.1080/15384101.2016.1160986
|View full text |Cite
|
Sign up to set email alerts
|

Skp2 is over-expressed in breast cancer and promotes breast cancer cell proliferation

Abstract: The F box protein Skp2 is oncogenic. Skp2 and Skp2B, an isoform of Skp2 are overexpressed in breast cancer. However, little is known regarding the mechanism by which Skp2B promotes the occurrence and development of breast cancer. Here, we determined the expression and clinical outcomes of Skp2 in breast cancer samples and cell lines using breast cancer database, and investigated the role of Skp2 and Skp2B in breast cancer cell growth, apoptosis and cell cycle arrest. We obtained Skp2 is significantly overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 40 publications
4
30
0
Order By: Relevance
“…Importantly, elevated levels of both p62 and Skp2 have been associated with therapeutic resistance 38 40 and as such. efforts are currently underway to identify small molecule inhibitors 37 , 39 , 41 43 to block their function and/or activity. While several reports indicate that autophagy plays a pro-survival role in a variety of cancers 44 , other studies indicate that autophagy induced by anti-neoplastic agents results in cell death 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, elevated levels of both p62 and Skp2 have been associated with therapeutic resistance 38 40 and as such. efforts are currently underway to identify small molecule inhibitors 37 , 39 , 41 43 to block their function and/or activity. While several reports indicate that autophagy plays a pro-survival role in a variety of cancers 44 , other studies indicate that autophagy induced by anti-neoplastic agents results in cell death 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the original identification of PHB1 as a proliferation suppressor in rat liver cells 1 , the effect of PHB1 on cancer proliferation has been studied. Some studies found that PHB1 inhibits breast cancer cell proliferation by up-regulating androgen receptor (AR) expression in estrogen receptor (ER)-positive breast cancer cells 15 , 63 . PHB1 also inhibits proliferation of human osteosarcoma MG-63 cells by interacting with tumor suppressors such as p53 64 .…”
Section: Role Of Phb1 and Phb2 In Tumorigenesismentioning
confidence: 99%
“…Analysis of the cell cycle and apoptosis was performed as described previously. [26][27][28][29] Each sample was tested in triplicate and untreated cells were used as controls.…”
Section: Cell Cycle and Apoptosis Analysismentioning
confidence: 99%